2015
DOI: 10.1530/rep-15-0129
|View full text |Cite
|
Sign up to set email alerts
|

Dexrazoxane exacerbates doxorubicin-induced testicular toxicity

Abstract: Infertility induced by anti-cancer treatments pose a major concern for cancer survivors. Doxorubicin (DXR) has been previously shown to exert toxic effects on the testicular germinal epithelium. Based upon the cardioprotective traits of dexrazoxane (DEX), we studied its potential effect in reducing DXR-induced testicular toxicity. Male mice were injected with 5 mg/kg DXR, 100 mg/kg DEX, combination of both or saline (control) and sacrificed either 1, 3 or 6 months later. Testes were excised and further process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 51 publications
(49 reference statements)
2
15
0
Order By: Relevance
“…Indeed, acute DOX administration causes multi-organ toxicity with potential interplay between different organs to alter sEH expression. Importantly, DOX administration has been shown to cause significant testicular toxicity and marked decrease in serum testosterone in experimental animals [3236]. In agreement with these studies, we found out that acute DOX administration caused a significant reduction of the testes weights in male mice 3 days after DOX administration, indicating DOX-induced testicular toxicity.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, acute DOX administration causes multi-organ toxicity with potential interplay between different organs to alter sEH expression. Importantly, DOX administration has been shown to cause significant testicular toxicity and marked decrease in serum testosterone in experimental animals [3236]. In agreement with these studies, we found out that acute DOX administration caused a significant reduction of the testes weights in male mice 3 days after DOX administration, indicating DOX-induced testicular toxicity.…”
Section: Discussionsupporting
confidence: 89%
“…Numerous studies had shown that different anticancer treatments including both chemotherapy or radiotherapy may disrupt spermatogenesis in various stages of life and may result in male infertility . Increased production of reactive oxygen species (ROS) and impairment of cellular antioxidant defence are associated with such damage.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous molecular pathways have been postulated to explain apoptosis, depending on the causes and specific tissue involved. Many investigators reported the pronounced increase in DNA‐fragmentation and testicular apoptosis after exposure to doxorubicin or irradiation . There is a prominent role for the activation of the mitochondrial pathway after irradiation injury to testis in rats .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We choose several indicators of testicular function: Testicular weight, correlated with the size of the seminiferous tubules and spermatogenesis; Epididymal weight, correlated to the amount of sperm accumulated after spermatogenesis; Sperm count and motility, both measures of the scale and quality of spermatogenesis, respectively; Serum AMH, indicator of chemotherapy-induced endocrinal imbalance in testes with no functional germ cells; Immunofluorescence staining, characterizing the chemotherapeutic effect on target testicular key cells of in the seminiferous tubules and serving as a measure of proliferation, meiotically activity and apoptosis; Testicular mRNA of ID4 or GFRA1 transcription factors, serving as markers for the key element in the testis, undifferentiated spermatogonia [ 18 ]. Oncofertility research has shown strong positive correlation between testicular function and all indicated parameters, aside from serum AMH and TUNEL, where negative correlation is observed [ 18 , 20 22 ]. Our results in the current study indicate correlating of these parameters with the same positive-negative orientation may strengthen the reliability and extant of the assessment of total testicular function.…”
Section: Discussionmentioning
confidence: 99%